Pola Hubungan Patron Klien Pada Komunintas Petani Rumput Laut di Desa Bungin Permai Kecamatan Tinanggea Kabupaten Konawe Selatan - Badriadi, Badriadi; Fausayana, Ine; Meisanti, Meisanti (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
This research aims to gain knownedge that whole and profound about the patterns of the patron-client relationships in the farming community of seaweed in the Bungin Permai Village using what became relations identifier of patron-client based on the theory of patron-client James C. Scott. This type of research is qualitative research using the postpositivisme paradigm. The methods used in this research is a method of triangulation analisys technique is done by comparing the information or data with different way. The technique of data collections was done through literature review, observation and in-depth interview with seaweed farming community in the village of Bungin Permai.Â  The results showed that the survival of the patron client relationship in Bungin Permai Village in the future between seaweed farmers with traders will continue or intertwined due to the deliberately constructed by both parties without any who feel harmed, although the patron client relationship itâ€™s seen not balanced. Patron client relationship in the Bungin Permai Village is the protection relationship between both parties who need each other though in unequal levels such as the patron gives a debt to the client, to reply by clients by selling yields only to the patrons and in addition, the client is also willing to help patrons if patrons need of assistance. The loyalty relationship between patron with clients in Bungin Permai Village occurs because each of them is already cultivating a trusting nature and patrons also always provides convenience to its clients. In addition to the factor of mutual trust, wich form patron client relationship between farmers with traders in the Bungin Permai Village is a familial factors